FREE BASIC EDUCATION BETWEEN CONSTITUTIONAL NORM AND IMPLEMENTATION REALITIES - I Gede Sujana; Ande Ana Konda; Febliana Dapa; Eldiyanto Tadu Niga (International Journal of Education and Social Science Studies, 2025)
This article examines the gap between the constitutional guarantee of free basic education in Indonesia and its practical implementation following the rulings of the Constitutional Court. Although the Court has affirmed the state's obligation to eliminate all forms of educational fees at the elementary and junior secondary levels, empirical evidence reveals the continued imposition of indirect costs on students and their families. These include informal charges for uniforms, school maintenance, extracurricular activities, and other operational needs. The study adopts a qualitative, descriptive-analytical approach using doctrinal legal analysis, field observations, and interviews with key stakeholders. Findings indicate that limited school funding, regulatory ambiguity, inconsistent regional policies, and a lack of legal awareness among citizens hinder the realization of truly free education. The article concludes that while Indonesia’s constitutional framework on education is normatively strong, its implementation requires comprehensive reforms involving fiscal equity, regulatory clarity, institutional accountability, and civic empowerment to ensure the right to free basic education becomes a lived reality for all.